Adoption of Startup Innovation Business: Bibliometric Analysis - Eko Restianto Yanuar; Krisnaresanti Aldila; Iskandar Dadang; Dinanti Aldila; Rifda Naufalin Lina; Chasanah Nur (E3S Web of Conferences)
This study identifies Brazil as the leading country in global publication frequency, followed by Indonesia in third place. The Proceedings of the European Conference on Innovation and Entrepreneurship (ECIE) is the most significant publication source, contributing three articles. The analysis spans from 2004, marking its initiation, to 2024, which records the highest annual scientific output with ten publications. The peak in average annual citations occurred in 2018, reflecting the impact of prior works. The findings highlight critical gaps in the existing literature and provide strategic guidance for future research. Motor themes, including sustainability, sustainable development, climate change, innovation, technology adoption, and business development, exhibit high levels of development (density) and relevance (centrality). These themes underscore the alignment of contemporary research with pressing global challenges, emphasizing their importance in addressing current and emerging discourses. This study contributes to the academic community by mapping research trends and identifying themes that warrant further exploration. By focusing on these highly relevant areas, future research can advance knowledge and address global challenges more effectively, fostering innovation and sustainable development.